1997
DOI: 10.4141/s96-053
|View full text |Cite
|
Sign up to set email alerts
|

Increased denitrification below the root zone in the fall following a spring manure application

Abstract: Increased denitrification below the root zone in the fall following a spring manure application. Can. J. Soil Sci. 77: 249-251. Indirect measurements of denitrification to 120 cm depth in a coarse textured soil in October showed higher denitrification rates following a single spring application of dairy cattle slurry than following a spring application of fertilizer. The highest denitrification rates occurred immediately above and below the water table (90 cm depth) and resulted primarily from C applied in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several authors have reported that available carbon rather than nitrate controlled denitri®cation rates (Myrold & Tiedje 1985;Comfort et al 1990;McCarty & Bremner 1992). Christensen (1983), Paul et al (1997) and Loro et al (1997) also found smaller N 2 O emissions from mineral fertilizer than from slurry, suggesting that the carbon added with the slurry probably affected denitri®cation rates mainly by providing an energy source for the denitrifying bacteria. In this way, Comfort et al (1988) indicated that only 10 to 15 days were required for the readily oxidizable carbon to be metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that available carbon rather than nitrate controlled denitri®cation rates (Myrold & Tiedje 1985;Comfort et al 1990;McCarty & Bremner 1992). Christensen (1983), Paul et al (1997) and Loro et al (1997) also found smaller N 2 O emissions from mineral fertilizer than from slurry, suggesting that the carbon added with the slurry probably affected denitri®cation rates mainly by providing an energy source for the denitrifying bacteria. In this way, Comfort et al (1988) indicated that only 10 to 15 days were required for the readily oxidizable carbon to be metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…Supply of C is ofi:en considered the major limiting factor for denitrification in subsoils . Dissolved organic C will also have leached with NO3", and there is evidence that a supply of leached C will support subsoil denitrification (Brye et al, 2001;Paul et al, 1997). Brye et al (2001) estimated that the maximum amount of NO3" that could be denitrified by C leached from prairie and cultivated soils was <25%, assuming that the dissolved organic C was labile and that anaerobic conditions existed.…”
Section: Denitrification and Nitrous Oxide Production In The Soil Promentioning
confidence: 98%
“…The effects of the treatments described here on growing season crop yield and N uptake, soil inorganic N levels at harvest , denitrification losses during the growing season (Paul and Zebarth 1996a), and leaching and denitrification losses during the fall and winter (Paul and Zebarth 1996b;Paul et al 1996) have been reported elsewhere.…”
mentioning
confidence: 95%